Strategi Pemasaran Digital 7P pada UMKM Fashion: Studi Empiris di Kota Medan - Nadila Jelita; Sri Ramadhani; Nuri Aslami (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
In the midst of digital disruption, local fashion MSMEs such as Vinaga Bag Medan Store face the challenge of limited product differentiation and less strategic physical locations in optimizing the 7P mix digital marketing strategy. This study analyzes marketing strategies through a mix of 7Ps (product, price, place, promotion, people, process, physical evidence) with a qualitative case study approach. Data was collected through in-depth interviews with four main sources of store owners, employees and offline and online customers, observation and analysis of internal documents related to the marketing of the Vinaga Bag Medan store. The results of the study demonstrate effective strategies for regular product updates, tiered pricing structures, influencer-based and social commerce promotions, and responsive service processes. However, the main obstacle lies in product differentiation and digital channel optimization. The implications of this study recommend diversifying sales channels, investing in digital HR training, phasing out private labels, and data-driven inventory management systems to strengthen the competitiveness of local fashion MSMEs amid digital disruption.